2022
DOI: 10.1186/s12873-022-00727-0
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making changes for patients and medical personnel in the management of acute appendicitis during the COVID-19 pandemic

Abstract: Background Acute appendicitis is the most common cause of acute abdomen. During the pandemic, to contain the spread of COVID-19, there were some integral changes in the medical processes based on the pandemic prevention policy, especially regarding emergency surgery. This study was conducted to investigate whether this pandemic also impacted the decision-making for both patients and medical personnel along with the treatment outcomes. Methods Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Previous studies have investigated the impact of the COVID-19 pandemic in the acute care setting on speci c countries (23,203,199,201), phases of the pathway (136, 201), or diseases (197,202,204). This scoping review provides a comprehensive overview of the changes reported on the quality of acute care during the rst year and a half of the COVID-19 pandemic, covering OECD countries, multiple diseases, and following a care pathway approach.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated the impact of the COVID-19 pandemic in the acute care setting on speci c countries (23,203,199,201), phases of the pathway (136, 201), or diseases (197,202,204). This scoping review provides a comprehensive overview of the changes reported on the quality of acute care during the rst year and a half of the COVID-19 pandemic, covering OECD countries, multiple diseases, and following a care pathway approach.…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence shows that antibiotic treatment for uncomplicated acute appendicitis is safe and efficient and results in major cost savings compared with surgery . The advantages of treating appendicitis without surgery and minimizing the associated length of hospitalization were further emphasized during the COVID-19 pandemic . These findings have had a major impact on the treatment strategies for acute appendicitis, making antibiotics a widely recognized feasible first-line treatment option .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] The advantages of treating appendicitis without surgery and minimizing the associated length of hospitalization were further emphasized during the COVID-19 pandemic. [8][9][10] These findings have had a major impact on the treatment strategies for acute appendicitis, 9,10 making antibiotics a widely recognized feasible first-line treatment option. 5 Furthermore, studies suggest that outpatient management of uncomplicated acute appendicitis could be a feasible option, leading to substantial cost savings and better allocation of hospital resources.…”
mentioning
confidence: 99%